Detainees in Police Custody in Yorkshire, United Kingdom: A Survey of the Common Mental Health Problems - Oluboku, Jibowu (International Journal of Criminology and Sociology, 2018)
Purpose: The purpose of this paper is to identify and study the common mental health problems presented by detainees in police custody as well their demographic characteristics. This would help to create awareness and sensitise health care practitioners working in custody, as well as custody staff towards early recognition and detection of cases, which should facilitate the health promotion and psycho social education of detainees and reduce the overall clinical risk in custody. Design/Methodology: The 'anonymised custody records' of a random sample of two hundred and fifty eight detainees in police custody as well as the Forensic Medical practitioners contemporaneous notes including 'direct clinical interviews 'were examined. Data was collected from the Risk assessment record completed by the custody officers and record of medical assessment by forensic Medical Examiners using a 'Standard Questionnaire format ‘. Data then was analysed. Findings: Detainees admitted into custody experienced a wide range of mental health problems.The most common mental health problems seen in detainees during the period of study were, substance misuse, depression, self-harm, anxiety disorder, epilepsy and schizophrenia in that order. Other conditions were identified such as Learning disabilities. The sex distribution was Male (83%) and Female (17%). In terms of age distribution most of the detainees were in the age range 20-41 (67.5%) for both sexes. The female detainees tend to be older compared to males.Heroin use was the most prevalent drug of abuse in custody. Some of the most common medications prescribed for detainees are Methadone, Mirtazapine, Citalopram, Diazepam, Sorbutex, sodium valproate and Thiamine. Originality/Value: The findings from this study would help to further identify and bring awareness to the common mental health problems encountered in detainees in police custody. It would help to reduce clinical risks and facilitate a safer detention in custody. It would also help to address the issue of the limited availability of data regarding the mental health of detainees.